An Analysis of Family Structures and Daily Life Among the Sea Tribe in Riau: A Cultural Perspective - Nurfitri, Rina; Fitri, Yolanda (IC-ITECHS, 2024)
This study explores the family structures and daily life of the Sea Tribe in Riau, focusing on their unique cultural practices, social dynamics, and adaptation to their maritime environment. The research employs a qualitative approach, utilizing ethnographic methods such as in-depth interviews, participant observation, and document analysis. The findings reveal that the Sea Tribe’s family structures are shaped by their communal living patterns, with strong kinship ties playing a central role in social organization and decision-making. Daily life revolves around traditional maritime activities, including fishing, boat building, and trading, which are integral to their economic and cultural identity. Furthermore, the study highlights the intergenerational transmission of knowledge and the role of rituals in strengthening familial and community bonds. Challenges such as modernization, environmental changes, and shifting socio-political landscapes are also examined, shedding light on how these factors impact their way of life. This research contributes to the understanding of indigenous maritime communities and emphasizes the importance of preserving the cultural heritage of the Sea Tribe in Riau amidst rapid global change